Avaliaç\~ao da deficiência para acesso a políticas públicas: Contribuiç\~oes para um instrumento unificado de avaliaç\~ao da deficiência - Liliane Cristina Gonçalves Bernardes; Miguel Abud Marcelino; Lailah Vasconcelos de Oliveira Vilela (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study discusses, in general terms, some instruments used in the assessment of disabilities, for eligibility and access to public policies in Brazil, with emphasis on the Modified Brazilian Functioning Index (IFBrM). The purpose is to elucidate certification procedures for this condition, contributing to the design of a unified assessment instrument, to be adopted by the government. Initially, it describes the historical context that documents efforts towards a unified national assessment method. Subsequently, suggestions for improving the IFBrM are presented, based on the conclusions of the validation process of this instrument. The discussion continues towards the feasibility of implementing a unified disability assessment system, with the aim of facilitating access to public policies and promoting more effective collaboration between federative entities. To conclude, in the annex, the components of the improved proposal for the disability assessment instrument are thoroughly outlined.
Keywords: I18; 330; disability; disability assessment; biopsychosocial; public policy; Modified Brazilian Functioning Index (IFBrM)